The Effect of Work-Life Balance and Motivation on Academic Performance: Case Study on 2021 Management Students Who Work Part-Time at Universitas Buana Perjuangan Karawang - Vigar Patria; Asep Jamaludin; Yeni Fajrin (International Journal of Economics and Management Research, 2025)
This study intends to examine the influence of Work-Life Balance (X1) and Motivation (X2) on Academic Performance (Y) with a quantitative approach utilizing multiple regression analysis methods. The research sample consisted of 97 respondents through the purposive sampling method. The results of the research prove that Work-Life Balance has a positive and significant effect on Academic Performance with a t-point of 4.673, a significance of 0.000 (p < 0.05), and a regression coefficient (Beta) of 0.424. In addition, Motivation also has a positive and significant effect on Academic Performance with a t-point of 4.125, a significance of 0.000 (p < 0.05), and a regression coefficient (Beta) of 0.374. Simultaneously, Work-Life Balance and Motivation can explain 51.2% variation in Academic Performance with an R Square point of 0.512 and a significant F test result (sig. 0.000). These findings confirm that work-life balance and academic life as well as optimal motivation play an important role in improving academic performance. The implications of this research prove its contribution to the development of theories regarding factors that affect academic performance and become a recommendation for educational institutions and the world of work in creating an environment that supports individual productivity and well-being.